2017
DOI: 10.5222/buchd.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for epilepsy after ischemic stroke in children

Abstract: Objective: We performed this study to determine the incidence of seizures and poststroke epilepsy and risk factors of post-stroke epilepsy after childhood ischemic stroke. Methods: In this study, we retrospectively analyzed data from children who had ischemic stroke. Results: Of the one hundred and two children, mean age of stroke onset was 67.32± 25.48 months (1-180 months). There were 56 (54.9%) boys and 46 (45.1%) girls in the study . Of the 102 patients, 39 (38.2%) had seizures. Twenty seven (69.2%) had ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Seizures after stroke appeared significantly more commonly in girls with TACI stroke, while only in one girl with LACI stroke and in the only girl with POCI stroke ( p = 0.022). A study performed in Turkey also demonstrated that post-stroke epilepsy was more common in AIS girls, whereas no significant sex differences were observed between AIS children with epilepsy and AIS children without epilepsy [ 33 ]. In the study by Laugesaar et al [ 34 ], cortical lesions, and involvement of the thalamus and temporal lobe, were reported to be independent predictors of post-stroke epilepsy in 73 children, of whom 53% were boys.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures after stroke appeared significantly more commonly in girls with TACI stroke, while only in one girl with LACI stroke and in the only girl with POCI stroke ( p = 0.022). A study performed in Turkey also demonstrated that post-stroke epilepsy was more common in AIS girls, whereas no significant sex differences were observed between AIS children with epilepsy and AIS children without epilepsy [ 33 ]. In the study by Laugesaar et al [ 34 ], cortical lesions, and involvement of the thalamus and temporal lobe, were reported to be independent predictors of post-stroke epilepsy in 73 children, of whom 53% were boys.…”
Section: Discussionmentioning
confidence: 99%